PENERAPAN SENAM KEGEL TERHADAP PENGURANGAN RASA NYERI LUKA PERINEUM IBU POST PARTUM DI PUSKESMAS MAOS CILACAP - Rahmawati, Rahmawati; Imanah , Norif Didik Nur; Aksar , Septi Tri; Sukmawati, Ellyzabeth (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Postpartum mothers with perineal wounds will feel pain and discomfort when doing activities or sitting. Kegel exercises can increase circulation in the perineum, thereby reducing pain and speeding up the healing process and reducing swelling, during vaginal delivery. This study aims to determine the application of Kegel exercises to reduce pain in perineal wounds in post-partum mothers using qualitative research with case studies and data sources and types of data using interviews and observations. The implementation technique was carried out on Mrs. M with a companion and instructions, namely doing movements such as holding in urination, holding the contraction for 6 seconds, releasing, this movement is done by lying on your back, repeating the movement several times for 20 minutes. The results of doing Kegel exercises for 20 minutes, Mrs. M felt a change in the pain in her perineal wound, indicating that the mother felt more relaxed. The conclusion based on the results of data analysis is that applying Kegel exercises can help reduce perineal wound pain in post-partum mothers. It is hoped that midwives at community health centers or health services will apply and provide complementary therapy to post-partum mothers to reduce pain due to perineal lacerations and to increase post-partum mothers' knowledge about Kegel exercises.